THE INFLUENCE OF TOTAL FINANCING, FINANCING RETURN PERIOD AND COLLATERAL VALUE ON THE SMOOTHNESS OF MURABAHAH FINANCING RETURNS (Empirical Study at KSPPS BMT Al-Kautsar Darmaraja Period 2019-2021) - Muhammad Azhar Fauzan; Shofia Annisa Ratnasari (SINTESA, 2023)
Smooth return of murabahah financing is based on the smoothness or failure of the debtor in paying the loan principal according to a predetermined time. This study aims to determine the effect of the amount of financing, the period of financing repayment and the guarantee value on the smooth return of murabahah financing (an empirical study at KSPPS BMT Al-Kautsar Darmaraja for the 2019-2021 period). The research method used is a quantitative method. The data used is in the form of secondary data, namely the financing report on KSPPS BMT Al-Kautsar Darmaraja for the 2019-2021 period. Sampling using purposive sampling technique as much as 70 data. Data were analyzed using multiple linear regression analysis on IBM SPSS Statistics 27.0 software. The results of the study show that the amount of financing, the period of repayment of financing and the value of the guarantee partially have no positive and significant effect on the smooth return of murabahah financing at KSPPS BMT Al-Kautsar Darmaraja for the 2019-2021 period, the amount of financing, the period of repayment of financing, and the total collateral value simultaneously has a positive and significant effect on the smooth return of murabahah financing at KSPPS BMT Al-Kautsar Darmaraja for the 2019-2021 period.